2007
DOI: 10.4049/jimmunol.179.3.1855
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary Delivery of Bone Marrow-Derived Mesenchymal Stem Cells Improves Survival and Attenuates Endotoxin-Induced Acute Lung Injury in Mice

Abstract: Recent in vivo and in vitro work suggests that mesenchymal stem cells (MSC) have anti-inflammatory properties. In this study, we tested the effect of administering MSC directly into the airspaces of the lung 4 h after the intrapulmonary administration of Escherichia coli endotoxin (5 mg/kg). MSC increased survival compared with PBS-treated control mice at 48 h (80 vs 42%; p < 0.01). There was also a significant decrease in excess lung water, a measure of pulmonary edema (145 ± 50 vs 87 ± 20 μl; p &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

57
850
9
10

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 830 publications
(934 citation statements)
references
References 37 publications
57
850
9
10
Order By: Relevance
“…13,24 A growing number of studies have shown that MSCs have immunomodulatory and anti-infl ammatory eff ects despite minimum or absent engraftment. [25][26][27][28] Consequently, research has shifted towards identifi cation of alternative pathways through which MSCs interact with host tissue, including interactions between cells, direct interactions with the host immune system, and mitochondrial transfer. The pathway with the most robust supporting evidence is the ability of MSCs to coordinate tissue repair through the release of soluble paracrine factors.…”
Section: Reviewmentioning
confidence: 99%
“…13,24 A growing number of studies have shown that MSCs have immunomodulatory and anti-infl ammatory eff ects despite minimum or absent engraftment. [25][26][27][28] Consequently, research has shifted towards identifi cation of alternative pathways through which MSCs interact with host tissue, including interactions between cells, direct interactions with the host immune system, and mitochondrial transfer. The pathway with the most robust supporting evidence is the ability of MSCs to coordinate tissue repair through the release of soluble paracrine factors.…”
Section: Reviewmentioning
confidence: 99%
“…In the context of alveolar tissue MSC have been shown to contribute to lung regeneration in numerous experimental settings, including homing and attenuation of endotoxininduced acute lung injury (Gupta et al 2007;Lee et al 2009). Promising potential of MSC has been studied in several ways and detectable therapeutic benefits were often attributed to paracrine mechanisms, since engraftment was low (van Haaften et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To further test the role of MSCs and LXA 4 in acute lung injury, we studied the effect of the ALX/FPR2 receptor agonist and antagonist using an in vivo experimental model of acute lung injury induced by LPS, a model we have used in a prior study (2). The percentage of apoptotic human MSCs at the time of i.t.…”
Section: Effects Of Human Mscs Recombinant Lxa 4 and Wrw4 On 48-h mentioning
confidence: 99%
“…Gravimetric lung water determination was done by standard methods as we have reported (2,25). Lungs from endotoxin injured with or without treatment with LXA 4 and MSCs were excised at 48 h. The lungs were inflated with 0.5 ml air and the trachea was ligated.…”
Section: Extravascular Lung Water and Lung Histologymentioning
confidence: 99%
See 1 more Smart Citation